The Corelation of Stress Level and Quality of Life of Elderly on Hypertension in Posyandu Elderly Village Sumberejo Gedangan Sub-District Malang District - Yuliani , Ika; Rohmi, Faizatur; Agustiningsih, Nia (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2024)
Elderly generally experience stress due to suffering degenerative disease that often occur that is hypertension. Stress appear on hypertensive patients caused by a sudden change in activities that are usually elderly do, the existence of regular treatment and behavior changes both physically and emotionally. The Research is to analys The Corelation of Stress Level and Quality of Life of Elderly on Hypertension in Posyandu Elderly Village Sumberejo Gedangan Sub-District Malang District. This present study used descriptive correlation design with cross sectional approach. This study was conducted on march 10, 2018 in Posyandu Elderly Village Sumberejo Gedangan Sub-District Malang District. The sample in this research were 20 respondents taken using purposive sampling technique. The data collected by using questionnaire PSS and WHOQOL-BREF of respondents. The data were analysed by using Spearman Rank (Rho). In conclusion, this research showed that there is a Corelation of Stress Level and Quality of Life of Elderly on Hypertension in Posyandu Elderly Village Sumberejo Gedangan Sub-District Malang District with value of p = 0.001 where p < ? (0.05). It is suggest elderly to recognize stress on her self so as to management the stress, always be grateful for what have been achieved and owned, perform physical activities such as gymnastics regularly because it proved to improve the quality of life both physically and mentally.